Use of auditory evoked potentials with electrical stimulation at the round window niche pre-operatively on a brain-injured patient: A case study. (2nd January 2021) - Huen, Myron; Lee, Jowan; Westerberg, Brian D.
Abstract : The current case study focuses on a brain-injured patient for whom a second, right-side cochlear implant (CI) was implanted four years after the patient was unable to obtain sound percept with the first, left-sided implant. Initial thoughts suggested that an auditory brainstem implant would be required given imaging results. Instead, the second cochlear implant was ultimately recommended based on repeatable electrophysiologic measurements obtained during promontory stimulation (PS) testing. Objectives: To highlight the effectiveness of using PS testing in conjunction with electrically evoked auditory evoked potentials (eAEPs) to help guide treatment plans in patients with limited behavioural responses. Methods: Case report on a 59-year-old male with traumatic brain injury. Electrophysiological measurements in conjunction with PS were performed. Results: eAEPs were obtained up to the thalamo-cortical region, supporting the viability of a CI in the non-implanted ear. Discussion & conclusion: Use of PS in conjunction with electrically evoked auditory evoked potentials can provide valuable information to guide clinical decisions regarding implantation.